Novel approaches to improving high temperature corrosion resistance - Schütze, Michael; Quadakkers, W. J. (CRC Press ; Woodhead Pub., 2008)
High-temperature corrosion is a major problem affecting sectors such as the power generation, aerospace and metal-working industries. This important book summarises a wide range of research on ways of dealing with this important problem. The first part of the book reviews ways of modifying alloys to improve high-temperature corrosion resistance. The second part discusses surface treatments such as pre-treatments and coatings. The third part of the book summarises research on testing for high-temperature corrosion resistance and the development of common testing standards. It also reviews research on the behaviour of alloys in a wide range of service conditions such as furnace and boiler environments. The final part of the book discusses ways of modelling high-temperature corrosion processes to improve material performance and service life. With its distinguished editors and team of contributors drawn from some of the leading centres of research in the field, Novel approaches to improving high-temperature corrosion resistance is a standard reference for all those studying and dealing with high-temperature corrosion. Summarises a wide range of research on ways of dealing with high-temperature corrosionDiscusses ways of modelling high-temperature corrosion processes to improve material performance and service lifeA standard reference for all those studying and dealing with high-temperature corrosion.
Keywords: Metals -- Effect of high temperatures on.; Corrosion and anti-corrosives.; elektronické knihy; electronic books